تحديد نسبة انتشار المكورات العنقودية الذهبية عند مرضى التحال الدموي في قسم الكلية الصناعية في مشفى الأسد الجامعي - لايقة, عنان; خميس, عطية; حسون, داليا (Latakia University Journal -Medical Sciences Series, 2019)
هدفت هذه الدراسة للتحري عن الحمل الأنفي للعنقوديات الذهبية عند مرضى التحال الدموي في قسم الكلية الصناعية في مشفى الأسد الجامعي في اللاذقية والكادر الطبي العامل فيه، ونسبة انتشارها، ودورها كعامل خطورة لإحداث إنتان دموي عند هؤلاء المرضى. شملت الدراسة 124 مشاركاً، متوسط أعمارهم (±1550.77) عاماً، بينهم 60 ذكراً و64 أنثى، كان منهم 110 مرضى و14 فرداً من الكادر الطبي، يخضع كل المرضى لجلستين أسبوعياً لمدة 3-4 ساعات، بمتوسط مدة تحال )21±25.50) شهراً، تمت الدراسة في الفترة الواقعة بين حزيران 2010 و أيار2011، وجمع 3 مسحات أنفية لكل المشاركين بالدراسة. وبنتيجة البحث بلغ معدل السحوبات الثلاثة على التوالي: (38.7% , 40.3% , 46.8%)، أما الحمل الدائم فقد سجّل أعلى معدل مقارنةً بالسلبي والمتقطع وهي على التوالي: (43.5%,38.7%, 17.7%)، وتبيّن بنتيجة التحليل العاملي ). (P.C.Aأن لكل من الحمل الأنفي الدائم للعنقوديات الذهبية وإنتان القثطرة المركزية دوراً هاماً في إحداث الإنتان الدموي عند هؤلاء المرضى، وبذلك تسمح لنا هذه الدراسة بتحديد مرضى التحال الدموي كمرضى ذوي خطورة عالية للإنتان الدموي بالعنقوديات الذهبية المحمولة أنفياً، وبالتالي ضرورة تنفيذ قواعد العقامة الفردية والجماعية وتوسيع نطاق العلاج والوقاية بتطبيق مراهم مضادة للعنقوديات الذهبية بشكل موضعي (داخل الأنف وعند مداخل القثاطر) في وحدة غسيل الكلى مع أهمية تعميم ذلك على المراكز الهامة في المشافي في سوريا. Objective :Our study aimed to investigate the nasal carriage of Staphylococcus aureus and its prevalence between hemodialysis patients and medical staff and its role as a risk factor in the occurance of bacteremia in hemodialysis department in Al-Assad Hospital. Materials and Methods: This study included 124 participants, with means an age of (50.77 ±15) years, containing 60 males and 64 females, a hundred and ten of them were patients and fourteen of them were members of the medical staff. All patients had undergone 3-4 hours hemodialysis secissions twice weekly, which means hemodialysis duration of (25.50 ± 21) months. The study spanned over the period from June 2010 till May 2011, and three nasal screens per participant were gathered. Results: The rate of three screens was respectively (38.7%, 40.3%, 46.8%), the Permanent carriage recorded the highest ratio compared to the negative and intermittent which rates were respectively (43.5%,38.7%, 17.7%), (P.C.A.) showed that the Permanent nasal carriage of Staphylococcus aureus and center catheter infection has a major role in the occurrence of bacteremia with those patients. Conclusion: This study allowed us to identify hemodialyzed patients who carry S.aureus as a high risk group to bacteremia, that appears to begin from endogenous origin in the nasal mucosa. Thus its necessary to implement individual and collective hygiene guidelines, and expand the treatment and preventing by applying anti Staphylococcus aureus ointment locally inside the nose and in the entrance of catheter in hemodialysis unit. However, it is essential to disseminate this to as many important centers in the Syrian hospitals as possible.